Biosystems Engineering II Linking Cellular Networks and Bioprocesses - Wittmann, Christoph.; Krull, Rainer. (Advances in Biochemical Engineering / Biotechnology, 2010)
-Morphology of Filamentous Fungi: Linking Cellular Biology to Process Engineering Using Aspergillus niger, By Rainer Krull, Christiana Cordes, Harald Horn, Ingo Kampen, Arno Kwade, Thomas R. Neu, and Bernd Nr̲temann; -Multi-Scale Spatio-Temporal Modeling: Lifelines of Microorganisms in Bioreactors and Tracking Molecules in Cells, By Alexei Lapin, Michael Klann, and Matthias Reuss; -Impact of Profiling Technologies in the Understanding of Recombinant Protein Production, By Chandran Vijayendran and Erwin Flaschel -Engineering the Escherichia coli Fermentative Metabolism, By M. Orencio-Trejo, J. Utrilla, M.T. Fernn̉dez-Sandoval, G. Huerta-Beristain, G. Gosset, and A. Martinez; -Modeling Languages for Biochemical Network Simulation: Reaction vs Equation Based Approaches, By Wolfgang Wiechert, Stephan Noack, and Atya Elsheikh; -Impact of Thermodynamic Principles in Systems Biology, By J.J. Heijnen;